Povidone iodine- antiseptic wound irrigation prior to skin closure at caesarean section to prevent surgical site infection: a randomised study - Patne, Gotami; Jadav, Pravinkumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Surgical site infection (SSI) is seen frequently in women undergoing caesarean sections for various indications leading to increase in morbidity amongst the patients in the postpartum period. Irrigation of the subcutaneous tissue before the skin closure with topical antibiotics, povidone iodine or saline has been shown to reduce the risk of SSI. This study was aimed to determine the efficacy of povidone iodine for irrigation of subcutaneous tissue in prevention of SSI. Methods: This study was performed on 200 subjects undergoing caesarean section who were randomised into two groups- one in which intervention in the form of povidone iodine irrigation was performed and the other in which it was not. The incidence of SSI was calculated in both the groups. Results: The overall incidence of wound infection in this study was 8.5%. In povidone iodine and no povidone iodine group, the incidence was found to be 9% and 8% respectively. Conclusions: There was no significant difference between wound infection rates between the povidone iodine and the no povidone iodine group (p value =0.799 by chi square test, chi square value =0.06).